Digyalipopeptide A, an antiparasitic cyclic peptide from the Ghanaian Bacillus sp. strain DE2B - Nartey, Adwoa P.; Dofuor, Aboagye K.; Owusu, Kofi B. A.; Camas, Anil S.; Deng, Hai; Jaspars, Marcel; Kyeremeh, Kwaku (Beilstein Journal of Organic Chemistry, 2022)
During the continued isolation of different bacteria from highly diverse, low human activity environments in Ghana and the subsequent characterization and biological activity studies of their secondary metabolites, we found both Gram-positive and Gram-negative Bacillus strains to be ubiquitous and widespread. One of such strains, the Ghanaian novel Bacillus sp. strain DE2B was isolated from rhizosphere soils collected from the Digya National Park in Ghana. Chromatographic purifications of the fermented culture extract of the strain DE2B, led to the isolation of a cyclic lipopeptide, digyalipopeptide A (1). Using 1D and 2D NMR data, mass spectrometry sequence tagging, advanced Marfey’s analysis, and the GNPS molecular networking we solved the full structure of digyalipopeptide A (1). We found that compound 1 is a member of a somewhat homologous series of peptides produced as a mixture by the strain containing the same amino acid sequence in the cyclic peptide backbone but differing only by the length of aliphatic fatty acid side chains. When tested against Trypanosoma brucei subsp. brucei strain GUTat 3.1 and Leishmania donovani (Laveran and Mesnil) Ross (D10), digyalipopeptide A (1) gave IC50 values of 12.89 µM (suramin IC50 0.96 µM) and 4.85 µM (amphotericin B IC50 4.87 µM), respectively. Furthermore, digyalipopeptide A (1) produced IC50 values of 10.07 µM (ampicillin IC50 0.18 µM) and 10.01 µM (ampicillin IC50 1.53 µM) for Staphylococcus aureus and Shigella sonnei, respectively. The selectivity and toxicity profile of compound 1 was investigated using normal cell lines, macrophages RAW 264.7. When tested against normal macrophages, compound 1 gave an IC50 value of 71.32 μM. Selectivity indices (SI) were obtained by calculating the ratio of the IC50 in RAW 264.7 to the IC50 in the respective microbe and neglected parasite. In the presence of RAW 264.7 cell lines, compound 1 was particularly selective towards Leishmania donovani (Laveran and Mesnil) Ross (D10) with an SI value of 14.71. The bioactivity studies conducted confirm the role of these cyclic lipopeptides as defense chemicals in their natural environment and their ability to be biologically active across different species.
Keywords: Leishmania; lipopeptides; molecular networking; sequence tagging; trypanosomes

Molecular Medical Microbiology - Cote, C. K.; Heffron, J. D.; Bozue, J. A.; Welkos, S. L.; Liu, D. (Bacillus anthracis and other Bacillus species, 2015)

(untitled) - Checinska, A.; Paszczynski, A.; Burbank, M. (Annu. Rev. Food Sci. Technol., 2015)

(untitled) - Cihan, A. C.; Tekin, N.; Ozcan, B.; Cokmus, C. (Braz. J. Microbiol., 2012)

(untitled) - Sansinenea, E.; Ortiz, A. (Biotechnol. Lett., 2011)

(untitled) - Harwood, C. R.; Mouillon, J.-M.; Pohl, S.; Arnau, J. (FEMS Microbiol. Rev., 2018)

(untitled) - Boottanun, P.; Potisap, C.; Hurdle, J. G.; Sermswan, R. W. (AMB Express, 2017)

Bacillus thuringiensis Biotechnology - Raddadi, N.; Crotti, E.; Rolli, E.; Marasco, R.; Fava, F.; Daffonchio, D. (The Most Important Bacillus Species in Biotechnology, 2012)

(untitled) - Kandi, V. (J. Med. Microb. Diagn., 2016)

Sustainable Aquaculture Techniques - Nemutanzhela, M. E.; Roets, Y.; Gardiner, N.; Lalloo, R. (The use and benefits of Bacillus based biological agents in aquaculture, 2014)

(untitled) - Shafi, J.; Tian, H.; Ji, M. (Biotechnol. Biotechnol. Equip., 2017)

(untitled) - Schallmey, M.; Singh, A.; Ward, O. P. (Can. J. Microbiol., 2004)

(untitled) - Elshaghabee, F. M. F.; Rokana, N.; Gulhane, R. D.; Sharma, C.; Panwar, H. (Front. Microbiol., 2017)

(untitled) - Osei, E.; Kwain, S.; Mawuli, G. T.; Anang, A. K.; Owusu, K. B. A.; Camas, M.; Camas, A. S.; Ohashi, M.; Alexandru-Crivac, C. N.; Deng, H.; Jaspars, M.; Kyeremeh, K. (Mar. Drugs, 2019)

(untitled) - Tetevi, G. M.; Kwain, S.; Mensah, T.; Camas, A. S.; Camas, M.; Dofuor, A. K.; Azerigyik, F. A.; Oluwabusola, E.; Deng, H.; Jaspars, M.; Kyeremeh, K. (Molbank, 2019)

(untitled) - Kwain, S.; Tetevi, G. M.; Mensah, T.; Camas, A. S.; Camas, M.; Dofuor, A. K.; Azerigyik, F. A.; Oluwabusola, E.; Deng, H.; Jaspars, M.; Kyeremeh, K. (Molbank, 2019)

(untitled) - Vijayasarathy, S.; Prasad, P.; Fremlin, L. J.; Ratnayake, R.; Salim, A. A.; Khalil, Z.; Capon, R. J. (J. Nat. Prod., 2016)

(untitled) - Ayon, N. J.; Sharma, A. D.; Gutheil, W. G. (J. Am. Soc. Mass Spectrom., 2019)

(untitled) - Dewapriya, P.; Prasad, P.; Damodar, R.; Salim, A. A.; Capon, R. J. (Org. Lett., 2017)

(untitled) - Wang, M.; Carver, J. J.; Phelan, V. V.; Sanchez, L. M.; Garg, N.; Peng, Y.; Nguyen, D. D.; Watrous, J.; Kapono, C. A.; Luzzatto-Knaan, T.; Porto, C.; Bouslimani, A.; et al. (Nat. Biotechnol., 2016)

(untitled) - Vargas, F.; Weldon, K. C.; Sikora, N.; Wang, M.; Zhang, Z.; Gentry, E. C.; Panitchpakdi, M. W.; Caraballo-Rodriguez, A. M.; Dorreistein, P.; Jarmusch, A. K. (Rapid Commun. Mass Spectrom., 2020)

(untitled) - Nothias, L.-F.; Petras, D.; Schmid, R.; Dührkop, K.; Rainer, J.; Sarvepalli, A.; Protsyuk, I.; Ernst, M.; Tsugawa, H.; Fleischauer, M.; Aicheler, F.; Aksenov, A. A.; et al. (Nat. Methods, 2020)

(untitled) - de Oliveira, J. A. M.; Williams, D. E.; Andersen, R. J.; Sarragiotto, M. H.; Baldoqui, D. C. (J. Braz. Chem. Soc., 2020)

(untitled) - Zhi, Y.; Wu, Q.; Xu, Y. (Sci. Rep., 2017)

(untitled) - Carrillo, C.; Teruel, J. A.; Aranda, F. J.; Ortiz, A. (Biochim. Biophys. Acta, Biomembr., 2003)

(untitled) - Buchoux, S.; Lai-Kee-Him, J.; Garnier, M.; Tsan, P.; Besson, F.; Brisson, A.; Dufourc, E. J. (Biophys. J., 2008)

(untitled) - Deleu, M.; Bouffioux, O.; Razafindralambo, H.; Paquot, M.; Hbid, C.; Thonart, P.; Jacques, P.; Brasseur, R. (Langmuir, 2003)